2015
DOI: 10.1002/jbm.a.35605
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic potential and synergistic effects of growth factors delivered from a bionic composite system

Abstract: Previous research has raised substantial controversy over the synergistic effects of exogenous growth factors, BMP-2 and bFGF, when used together for the treatment of bony defects. Thus, this study evaluated the effects of BMP-2 and bFGF at specified dose ratio composited with n-HA/PU40, a porous scaffold material, for repairing femoral defect in rats. Four weeks after implantation of this composite system, tissue specimens were collected for histological, immunohistochemical examinations, and µ-CT scanning. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…It is a preferable strategy for other GFs to accompany FGF in order to obtain a promising outcome. Chen et al (2016) chose gelatin microspheres as BMP-2 and basic FGF (bFGF) carriers, which were further embedded in a commercialized injectable thermal-sensitive hydrogel. The hydrogel was injected into a porous cell-loading scaffold before use.…”
Section: Fibroblast Growth Factor (Fgf)mentioning
confidence: 99%
“…It is a preferable strategy for other GFs to accompany FGF in order to obtain a promising outcome. Chen et al (2016) chose gelatin microspheres as BMP-2 and basic FGF (bFGF) carriers, which were further embedded in a commercialized injectable thermal-sensitive hydrogel. The hydrogel was injected into a porous cell-loading scaffold before use.…”
Section: Fibroblast Growth Factor (Fgf)mentioning
confidence: 99%
“…Various growth factors, osteogenic proteins, and modified small molecule active peptides have been designed and synthesized. Osteogenic‐related active factors include vascular endothelial growth factor (Huang, Kaigler, Rice, Krebsbach, & Mooney, ), basic fibroblast growth factor (Chen et al, ), platelet‐derived growth factors (Andrae, Gallini, & Betsholtz, ), insulin‐like growth factor (Rico‐Llanos, Becerra, & Visser, ). Osteogenic‐associated proteins consist of bone morphogenetic protein‐2 (BMP‐2; Sun et al, ; Zhan, Liu, & Yu, ), parathyroid hormone (PTH; Khundmiri, Murray, Lederer, & Vitamin, ), and enamel matrix protein derivative (Shahriari, Houshmand, Razavian, Khazaei, & Abbas, ).…”
Section: Introductionmentioning
confidence: 99%
“…A second strategy for improving the regenerative potential of the BMP‐based tissue engineering implants is derived from numerous studies reporting that combinations of BMPs with certain other cytokines can enhance the osteogenic differentiation of progenitor cells in vitro and increase or accelerate bone formation in vivo because of additive or synergistic effects. A great variety of combinations have been tested, especially with mitogenic or angiogenic cytokines such as basic fibroblast growth factor‐2 (FGF‐2), vascular endothelial growth factor (VEGF), or epidermal growth factor (EGF), and most of them resulted in significant improvements compared with the use of single growth factors . Taking this into account, an interesting candidate molecule to improve the collagen‐BMP system for bone regenerative medicine is the insulin‐like growth factor‐1 (IGF‐1), which is a growth‐promoting cytokine that plays an important role in development, metabolism and growth .…”
Section: Introductionmentioning
confidence: 99%
“…A great variety of combinations have been tested, especially with mitogenic or angiogenic cytokines such as basic fibroblast growth factor-2 (FGF-2), vascular endothelial growth factor (VEGF), or epidermal growth factor (EGF), and most of them resulted in significant improvements compared with the use of single growth factors. 14,[17][18][19][20][21] Taking this into account, an interesting candidate molecule to improve the collagen-BMP system for bone regenerative medicine is the insulin-like growth factor-1 (IGF-1), which is a growth-promoting cytokine that plays an important role in development, metabolism and growth. 22 Knockout mice models have shown that IGF-1 deficiencies have strong influence on the normal embryonic and postnatal skeletal development and that the lack of this growth factor produces animals with dwarf phenotype, lower bone formation rates, hypomineralization of the skeleton and abnormal chondrogenesis in the growth plates.…”
Section: Introductionmentioning
confidence: 99%